Tracking Cefoperazone/Sulbactam Resistance Development In vivo in A. baumannii Isolated from a Patient with Hospital-Acquired Pneumonia by Whole-Genome Sequencing - Liu, Xiaofen; Zheng, Huajun; Zhang, Weipeng; Shen, Zhen; Zhao, Miao; Chen, Yuancheng; Sun, Li; Shi, Jun; Zhang, Jing (Frontiers in Microbiology, 2016)
Cefoperazone/sulbactam has been shown to be efficacious for the treatment of infections caused by Acinetobacter baumannii; however, the mechanism underlying resistance to this synergistic combination is not well understood. In the present study, two A. baumannii isolates, AB1845 and AB2092, were isolated from a patient with hospital-acquired pneumonia before and after 20 days of cefoperazone/sulbactam therapy (2:1, 3 g every 8 h with a 1-h infusion). The minimum inhibitory concentration (MIC) of cefoperazone/sulbactam for AB1845 and AB2092 was 16/8 and 128/64 mg/L, respectively. Blood samples were collected on day 4 of the treatment to determine the concentration of cefoperazone and sulbactam. The pharmacokinetic/pharmacodynamic (PK/PD) indices (%T>MIC) were calculated to evaluate the dosage regimen and resistance development. The results showed that %T>MIC of cefoperazone and sulbactam was 100% and 34.5% for AB1845, and 0% and 0% for AB2092, respectively. Although there was no available PK/PD target for sulbactam, it was proposed that sulbactam should be administered at higher doses or for prolonged infusion times to achieve better efficacy. To investigate the mechanism of A. baumannii resistance to the cefoperazone/sulbactam combination in vivo, whole-genome sequencing of these two isolates was further performed. The sequencing results showed that 97.6% of the genome sequences were identical and 33 non-synonymous mutations were detected between AB1845 and AB2092. The only difference of these two isolates was showed in sequencing coverage comparison. There was a 6-kb amplified DNA fragment which was three times higher in AB2092, compared with AB1845. The amplified DNA　fragment containing the blaOXA-23 gene on transposon Tn2009. Further quantitative real-time PCR results demonstrated that gene expression at the mRNA level of blaOXA-23 was >5 times higher in AB2092 than in AB1845. These results suggested that the blaOXA-23 gene had higher expression level in AB2092 via gene amplification and following transcription. Because gene amplification plays a critical role in antibiotic resistance in many bacteria, it is very likely that the blaOXA-23 amplification results in the development of cefoperazone/sulbactam resistance in vivo.